Exploitation of Pragmatic Aspects in Indonesian Humorous Discourses - Wijana, I Dewa Putu (Universitas Sanata Dharma, 2017)
This paper is intended to analyze and describe various pragmatic aspects exploited by humorous discourse creators in creating jocular texts in Indonesian. By assuming that nearly all jokes are created through a non bona fide process of communication, in which cooperative and politeness principles are intentionally violated in various ways, there must be extensive exploitations of pragmatic aspects. The examples are many kinds of speech acts, presupposition, pragmatic implicature, etc. found in Indonesian humorous discourse to create activities. All of these aspects so far have not been seriously studied by Indonesian linguists, especially whose works concern with humorous discourses.Key words: humor, discourse, text, pragmatics.Â Â